short-term operational planning model for natural gas production systems - Selot, Ajay; Kuok, Loi Kwong; Robinson, Mark; Mason, Thomas L; Barton, Paul I (AIChE journal, 2008)
A short-term operational planning model for natural gas production systems can help identify a consistent operational policy that satisfies contractual rules and customer specifications. Formulating and solving such a model poses challenges due to nonlinear pressure-flowrate relations, a multicommodity network and complex production-sharing contracts (PSC). A production allocation model is presented that can be viewed as a contractual model superimposed on an infrastructure model. The infrastructure model incorporates nonlinear pressure-flowrate relationships for wells and pipelines, multiple qualities of gas in the trunkline network and models of facilities. The contractual model is a mathematical representation of the PSC and associated operational rules. The model features are inspired by the Sarawak Gas Production System (SGPS) in East Malaysia. A case study similar to the Sarawak Gas Production System (SGPS) is presented. The final formulation is a nonconvex mixed-integer nonlinear program and is solved with GAMS/BARON to global optimality. A hierarchical multiobjective operational study is also presented. © 2007 American Institute of Chemical Engineers AIChE J, 2008